Pola Penguasaan Dan Upaya Penataan Lingkungan Tanah Wedikengser Di Tepi Sungai Code Dalam Rangka pelaksanaan Otonomi Daerah Di Yogtakarta - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2003)
This research was conducted in Yogyakarta Municipality, aiming at answering the questions: (1) How is the pattern of use and tenure of land in flood plain area of Code River?